Penggunaan Aplikasi SAP dalam Persiapan Uji Sertifikasi Kompetensi ERP - A, Affira Afri; Slamet, Muhammad Ramadhan; Wulandari, Febrina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2024)
The aim of this research is to determine the influence of student motivation, instructor support, and system quality on student satisfaction with learning in preparing for competency tests at the Batam State Polytechnic. This research uses quantitative methods. The sample for this research is students from the 2020 Batam State Polytechnic Managerial Accounting Study Program who have received the SAP Fundamentals course and are handled by teaching assistants. The data analysis technique used is multiple linear regression analysis using the SPSS version 26 statistical test tool. The results of research on all independent variables, namely student motivation and system quality, show that these results have a significant influence on student satisfaction as the dependent variable, but for the perceived instructor support. Based on the findings of this research, suggestions for further research are to add variables that were not explained in this research and expand the research sample